Imaging-based characterization of tumoral heterogeneity for personalized cancer treatment = Charakterisierung der Tumorheterogenität mittels bildgebender Verfahren zur personalisierten Krebsbehandlung - Haag, Florian; Hertel, Alexander; Tharmaseelan, Hishan; Kuru, Mustafa; Haselmann, Verena; Brochhausen, Christoph; Schönberg, Stefan; Froelich, Matthias F. (Nuklearmedizin, 2025)
With personalized tumor therapy, understanding and addressing the heterogeneity of malignant tumors is becoming increasingly important. Heterogeneity can be found within one lesion (intralesional) and between several tumor lesions emerging from one primary tumor (interlesional). The heterogeneous tumor cells may show a different response to treatment due to their biology, which in turn influences the outcome of the affected patients and the choice of therapeutic agents. Therefore, both intra- and interlesional heterogeneity should be addressed at the diagnostic stage. While genetic and biological heterogeneity are important parameters in molecular tumor characterization and in histopathology, they are not yet addressed routinely in medical imaging. This article summarizes the recently established markers for tumor heterogeneity in imaging as well as heterogeneous/mixed response to therapy. Furthermore, a look at emerging markers is given. The ultimate goal of this overview is to provide comprehensive understanding of tumor heterogeneity and its implications for radiology and for communication with interdisciplinary teams in oncology.
Artikel online veröffentlicht: 26. November 2025
Gesehen am 15.01.2026